Menuju Masa Depan Perbankan Berkelanjutan: Menelaah Pengaruh Green Banking Terhadap Nilai Perusahaan - Harika Putri, Made Ayu Chandra Dewi; Kusuma, Putu Sri Arta Jaya (Program Studi Akuntansi PSDKU Universitas Pattimura, 2024)
This study aims to examine the impact of green banking on firm value. The study employs purposive sampling with specific criteria, resulting in 40 samples consisting of 20 banks listed on the Indonesia Stock Exchange during the 2020-2021 period. Simple linear regression analysis is the data analysis method employed, with company value serving as the dependent variable and green banking serving as the independent variable. The study's conclusions suggest that the value of a company is not much impacted by green banking.